Analisis Hukum Bagi Pihak yang Melanggar Perjanjian Bisnis Apabila Ditinjau dari Aspek Hukum Perdata - Laksmi Candra Diptya; Rahandy Rizki Prananda (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study examines the analysis of civil law against parties who violate business agreements. The research method used is normative juridical study, namely research studies based on legal sources such as laws and regulations, and expert opinions to research studies related to the title chosen by the researcher. The results of this research are known that the business world, especially related to business agreements, is very prone to negligence or violations of the agreements that have been agreed upon. In law, this activity is referred to as default. Negligence or violations that occur are generally committed by one of the parties included in the agreement, causing losses in both material and non-material forms. Parties who violate the agreements that have been agreed upon can be entangled in various articles in the Civil Code. Some rules that may ensnare parties who violate the contents of this business agreement include Article 1236, Article 1239, Articles 1243, 1246 to Article 1250. These are articles in civil law that relate to breaches of agreements or defaults. Keywords: Business, Civil Law, Violation, Agreement